TINJAUAN KEMAMPUAN BERMAIN BOLA VOLI PADA PEMAIN CLUB AREMBANG SUNGAI ABANG - DEKA ISMI MORI SAPUTRA; Yahfenel Evi Fussalam; Ridho Kurniawan (PRODI PJKR UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2021)
ABSTRACT This research is motivated by problems related to the achievements of the Arembang Sungai Abang club volleyball players who are not yet optimal. This is because the basic techniques of playing volleyball have not been fully mastered. This type of research is descriptive quantitative. The purpose of this study is to describe how to analyze basic technical errors in playing volleyball. The sample in this study was the 22 active Arembang Sungai Abang club volleyball players. The instruments used are passing, top serve and smash tests. The data analysis technique used in this research is descriptive and quantitative in the form of percentages.Based on the results of the study, it can be concluded that. The dominant level of passing skills possessed by Arembang Volleyball Club players, Sungai Abang Sarolangun, is 1.7-80.5, which is quite good. (36.36%) The level of passing ability that is dominantly owned by the Arembang Sungai Abang Sarolangun Volleyball Club players is 48.7-56.5 belonging to the good category (40.90%). The dominant level of service ability possessed by the Arembang Sungai Abang Sarolangun Volleyball Club players is 13.3-1452 belonging to the less category (31.80%). The dominant level of smash ability of Arembang Volleyball Club players, Sungai Abang Sarolangun, is 13.9-15.7 belonging to the less category (36.36%).Keywords: Analysis, passing, smash, serve, volleyball